The rise of Clostridioides difficile infections and fall of associated mortality in hospitalized advanced cirrhotics. (12th March 2019) - Rosenblatt, Russell; Mehta, Amit; Cohen‐Mekelburg, Shirley; Shen, Nicole; Snell, David; Lucero, Catherine; Jesudian, Arun; Fortune, Brett; Crawford, Carl V.; Kumar, Sonal
Abstract: Background & Aims: Cirrhotics are at increased risk of Clostridioides difficile infection (CDI) and its associated high morbidity and mortality. However, the impact of CDI in cirrhotics over time remains unclear. This study analyses prevalence and mortality in CDI in hospitalized patients with advanced cirrhosis over 15 years and identifies trends. Methods: Using the Nationwide Inpatient Sample (NIS) from 1998 to 2014, 3 049 696 weighted patients with advanced cirrhosis (defined as evidence of decompensation or oesophageal varices) were identified using a validated algorithm of ICD‐9‐CM codes and included in the study. Trends were analysed using Cochran Armitage test and joinpoint regression and compared to the general population. Multivariable logistic regression was performed controlling for risk factors that affect mortality in cirrhotics. Results: CDI prevalence in advanced cirrhotics increased from 0.8% to 2.6%, annual percent change (APC) 8.8% (compared to 7.6% for the general population), while CDI‐related mortality decreased from 20.7% to 11.3%, APC −3.4% (compared to −2.0% for the general population), from 1998 to 2014. CDI independently increased mortality in advanced cirrhotics (OR 1.47, P  < 0.001) and was associated with acute kidney injury (AKI) (OR 2.09, P  < 0.001), which itself significantly increased mortality (OR 4.54, P  < 0.001). Hepatic encephalopathy and Hispanic ethnicity were interestingly associated with a lower prevalence of CDI. Conclusions: CDI is increasingly common in advanced cirrhotics, but on the contrary, its associated mortality is decreasing. Despite improvements in outcomes in patients with advanced cirrhosis, CDI is associated with an increased mortality, driven by AKI, and therefore, requires aggressive identification and therapy.